1997
DOI: 10.1542/peds.100.4.633
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Extremely Low Birth Weight Infants (500 to 999 Grams) Over a 12-Year Period

Abstract: In this study of ELBW infants, low birth weight was not associated with abnormal outcome. The risk factors of ICH III-IV/cystic PVL, chronic lung disease, and high social risk were associated with abnormal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(73 citation statements)
references
References 14 publications
5
63
0
5
Order By: Relevance
“…[35][36][37][38] These findings are somewhat reassuring in that we did not see differences in neurologic or cognitive outcome related to rHuEPO treatment. However, the size of the sample was not large enough to detect with certainty an adverse effect that is rare.…”
Section: Discussionsupporting
confidence: 54%
“…[35][36][37][38] These findings are somewhat reassuring in that we did not see differences in neurologic or cognitive outcome related to rHuEPO treatment. However, the size of the sample was not large enough to detect with certainty an adverse effect that is rare.…”
Section: Discussionsupporting
confidence: 54%
“…Embora, esse fator cause preocupação entre os profissionais que atuam junto a essa criança devido a possíveis seqüelas, como por exemplo, decorrentes do uso prolongado da oxigenoterapia que pode acarretar o aparecimento de retinopatias e entre outros problemas: déficit cognitivo, prejuízos neurológico e sensorial (Piecuch, Leonard, Cooper & Sehring, 1997), sendo encontradas quatro crianças no grupo MBP com déficit sensorial auditivo, nessa amostra. Além disso, o nível cognitivo das crianças na faixa etária estudada, em geral, não apresentou-se comprometido, tendo em vista o desempenho alcançado no Raven revelando que a maioria apresenta um nível intelectual médio.…”
Section: Discussionunclassified
“…Such an inverse relationship was previously demonstrated for the incidence of major disabilities in very preterm and/or VLBW children 67 and is related to the risk for disruption in cortical development (corticogenesis) and brain connectivity, which increases when BW and GA decrease. 68 For the extremely preterm or extremely low BW infants, adverse concomitant sequelae (such as abnormal cerebral ultrasound findings, chronic lung disease, and postnatal steroid administration), may explain abnormal neurodevelopmental outcomes in addition to BW and GA. 69,70 It has been questioned whether academic underachievement, behavioral problems, and neurocognitive dysfunction in very preterm and/or VLBW children improve or worsen over time. 6 Some studies have found evidence in support for the idea that the gap between very preterm and/or VLBW children and term-born peers becomes smaller with increasing age.…”
Section: Bw and Gamentioning
confidence: 99%